Policy change and learning in the RBC model - Mitra Kaushik; George W. Evans; Seppo Honkapohja (Bank of Finland, 2011)
What is the impact of surprise and anticipated policy changes when agents form expectations using adaptive learning rather than rational expectations? We examine this issue using the standard stochastic real business cycle model with lump-sum taxes. Agents combine knowledge about future policy with econometric forecasts of future wages and interest rates. Both permanent and temporary policy changes are analyzed. Dynamics under learning can have large impact effects and a gradual hump-shaped response, and tend to be prominently characterized by oscillations not present under rational expectations. These fluctuations reflect periods of excessive optimism or pessimism, followed by subsequent corrections.
URN:NBN:fi:bof-20140807530
Keywords: E62; D84; E21; E43; 330; taxation; government spending; expectations; permanent and temporary policy changes